Effect of one-week oral or inhaled salbutamol treatment with washout on repeated sprint performance in trained subjects - Eibye, K.; Jacobson, G. A.; Bengtsen, K.; Jessen, S.; Backer, V.; Bangsbo, J.; Hostrup, M. (Translational Sports Medicine, 2021)
Background: Acute and chronic supratherapeutic treatment with the commonly used beta2-agonist salbutamol has the potential to enhance sprint performance and muscle strength. However, little is known about the performance effects of short-term daily permitted inhaled treatment vs oral prohibited treatment in accordance with the 2020 Prohibited List issued by the World Anti-Doping Agency (WADA). Methods: Herein, we investigated the effect of twice-daily treatment with 400 µg inhaled or 4 mg oral salbutamol for 1 week on repeated sprint performance in 19 healthy well-trained men and women utilizing a randomized open-label crossover design. Before and after each treatment period, and a 12-16 hours washout to avoid an acute effect of salbutamol, subjects performed a repeated sprint test (3 × 30-second Wingate). Results: Neither oral nor inhaled salbutamol enhanced peak power (oral; 3.0 W; 95% CI -6.8 to 12.8 W; and inhaled; -3.8 W; 95% CI -14.3 to 6.8 W) or mean power (oral; -2.1 W; 95% CI -4.7 to 8.9 W and inhaled; -1.6 W; 95% CI -5.6 to 8.9 W) during the repeated sprint test irrespective of gender. Conclusions: These findings indicate that 1 week is insufficient for salbutamol to induce any relevant effect on repeated sprint performance in trained individuals.